The ethylene response factor VaERF092 from Amur grape regulates the transcription factor VaWRKY33, improving cold tolerance - Sun, Xiaoming; Zhang, Langlang; Wong, Darren C. J.; Wang, Yi; Zhu, Zhenfei; Xu, Guangzhao; Wang, Qingfeng; Li, Shaohua; Liang, Zhenchang; Xin, Haiping (The Plant journal : for cell and molecular biology, 2019)
Summary Cold stress is a major limiting factor in grape (Vitis) productivity. In this study, we characterized a cold‐responsive ethylene response factor (ERF) transcription factor, VaERF092, from Amur grape (Vitis amurensis). VaERF092 expression was induced by both low temperatures and the ethylene precursor 1‐aminocyclopropane‐1‐carboxylate (ACC), but was suppressed by treatment with the ethylene inhibitor aminoethoxyvinylglycine (AVG) under cold conditions. Ectopic expression of VaERF092 in Arabidopsis thaliana enhanced cold tolerance. Co‐expression network analysis of V. vinifera genes indicated that WRKY33 might be a downstream target of VaERF092. This hypothesis was supported by the fact that VaWRKY33 was expressed temporally after VaERF092 expression and could also be induced by cold and ACC, and inhibited by AVG. Yeast one‐hybrid, transient β‐glucuronidase (GUS) and dual‐luciferase reporter assays provided evidence for an interaction between VaERF092 and a GCC‐box element in the VaWRKY33 promoter. In addition, heterologous overexpression of VaWRKY33 in A. thaliana resulted in enhanced cold tolerance. VaERF092‐ and VaWRKY33 overexpressing grape calli showed lower low‐temperature exothermic values than the empty vector (EV) calli, indicating enhanced tolerance to cold. Together, these results indicated that VaERF092 regulates VaWRKY33 through binding to its promoter GCC‐box, leading to enhanced cold stress tolerance. Significance Statement Our study revealed that ethylene response factor VaERF092 regulated VaWRKY33 through binding to its promoter GCC‐box, leading to enhanced cold tolerance. This finding may provide a model responding to cold stress in plants.